2008
DOI: 10.1590/s1413-86702008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the use of imipenem at a University Hospital following the restructuring of an antimicrobial audit system

Abstract: This study analyzed the use pattern of imipenem following the restructuring of the antimicrobial audit system at a University Hospital. It was an observational study before and after the restructuring of the antimicrobial audit system in a University Hospital from May to August and then from September to December 2006. The criteria of the rational use of imipenem were obtained from a non-systematic revision of the literature. The collection of data on the general characteristics and clinical state of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Among the studies that analyzed antibiotic consumption using the DDD, we found that according to 5 of the 16 results for antibiotic use (each represented by a column in Tables 3 and 4 since a study may have evaluated the consumption of more than one site or treatment), third-generation cephalosporins were not among the three most used classes of antibiotics. Notably, two of them (2/5) were applied to calculate the consumption of antibiotics prescribed for infections caused by sensitive or resistant Staphylococcus aureus 29 and one for Pseudomonas aeruginosa 36 , while another evaluated only the use of imipenem 41 , and the last one calculated the antibiotic consumption of an entire hospital over four months 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies that analyzed antibiotic consumption using the DDD, we found that according to 5 of the 16 results for antibiotic use (each represented by a column in Tables 3 and 4 since a study may have evaluated the consumption of more than one site or treatment), third-generation cephalosporins were not among the three most used classes of antibiotics. Notably, two of them (2/5) were applied to calculate the consumption of antibiotics prescribed for infections caused by sensitive or resistant Staphylococcus aureus 29 and one for Pseudomonas aeruginosa 36 , while another evaluated only the use of imipenem 41 , and the last one calculated the antibiotic consumption of an entire hospital over four months 39 .…”
Section: Resultsmentioning
confidence: 99%
“…This review included 23 articles with different methodological designs. The main objective of seven studies was to analyze antibiotic use 20 , 25 , 26 , 28 , 30 , 39 , 42 , while the others presented this data secondary to a main objective, namely: to investigate the relationship between antibiotic consumption and the incidence of resistant bacteria 27 , 35 , 36 , assess indicators of rational drug use in antibiotic prescriptions 34 , assess the adequacy of antibiotic prescriptions by disease or microorganism 31 , 32 , compare antimicrobial therapy with the microorganisms’ sensitivity profile 22 , 26 , 29 , 37 , and assess the impact of implementing interventions in antibiotic consumption 24 , 33 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%